MENINGKATKAN AKTIVITAS BELAJAR DAN HASIL BELAJAR SISWA MELALUI METODE GROUP INVESTIGATION (GI) PADA MATERI MEMAHAMI SALING KETERGANTUNGAN PADA EKOSISTEM - Bambang Suprayogi (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2016)
ABSTRACTCoverage of the subject matter in addition to a lot of biology and spacious, and most of the material using the Latin or foreign languages. The learning is still conventional, so many students are experiencing ksesulitan for the study, causing the value of these subjects average value below the value specified KKM school, which is 75. The solution to overcome this problem researchers use learning methods Group Investigation. This action research conducted at SMP Negeri 1 Nganjuk with research samples VII.3 classes in the academic year 2014/2015 the number of students 30 people. This research was conducted during March 2015. May s.d learning activity data obtained through observations by researchers, while learning achievement obtained through tests conducted at the end of each cycle. Based on research data can be summarized in one cycle of 30 students, there are 18 students have not completed their study or not reaching the KKM (â‰¥ 75) with a percentage of 80% and 12 students completed with a percentage of 40% with an average value of class 62. In cycle 2 the average value of student activity increased to 85.0%, and all aspects of student learning activities lowest value B with excellent category, while the average value of the class became 84.56 and there was one student who falls below the KKM. The conclusion of this study is the Group Investigation learning methods can enhance students' learning activities and academic achievement. The research activity of this class action teachers will be motivated, to always improve student learning outcomes in all biological materials. To further solidify the concept that has been owned by the students, teachers can fuse with the GI method puzzle game play. The technique according to the nature of junior high school kids who still love to play, but they did not abandon the obligation of learning. KEYWORDS: student learning activities, learning outcomes and learning methods Group Investigation